An availability study of electronic articles in an academic health sciences library - Crum, Janet A (Medical Library Association, 2011)
OBJECTIVES: The purposes of this study were: to determine the number of articles requested by library users that could be retrieved from the library's collection using the library catalog and link resolver, in other words, the availability rate; and to identify the nature and frequency of problems encountered in this process, so that the problems could be addressed and access to full-text articles could be improved. METHODS: A sample of 414 requested articles was identified via link resolver log files. Library staff attempted to retrieve these articles using the library catalog and link resolver and documented access problems. RESULTS: Staff were able to retrieve electronic full text for 310 articles using the catalog. An additional 21 articles were available in print, for an overall availability rate of nearly 80%. Only 68% (280) of articles could be retrieved electronically via the link resolver. The biggest barriers to access in both instances were lack of holdings and incomplete coverage. The most common problem encountered when retrieving articles via the link resolver was incomplete or inaccurate metadata. CONCLUSION: An availability study is a useful tool for measuring the quality of electronic access provided by a library and identifying and quantifying barriers to access.